1976
DOI: 10.1029/jb081i023p04285
|View full text |Cite
|
Sign up to set email alerts
|

Inferred geologic settings and differentiation in basalts from the Deep-Sea Drilling Project

Abstract: Petrographic and geochemical studies of basalt glass and related rocks from the Deep‐Sea Drilling Project (DSDP) provide a random sampling of magmas which have crystallized to form sea floor basement rocks. The samples range in age from 155 m.y. to less than 4 m.y. and represent a variety of geologic settings within the three major ocean basins. The majority show the mineralogy, textures, and large‐ion lithophile (LIL) element‐depleted characteristics of modern basalts from mid‐ocean spreading ridges (group I)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
3

Year Published

1977
1977
1996
1996

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(85 citation statements)
references
References 26 publications
3
78
1
3
Order By: Relevance
“…These rocks are unusually depleted in incompatible elements ( Fig. 5; Group D, TiO 2 = 0.7%-1.2%, Nb < 0.5-1.2 ppm, and Zr = 34-60 ppm), but have incompatible element ratios similar to normal I-type MORB as defined by Bryan et al (1976). The refractory nature of these basalts is.…”
Section: Igneous Petrology and Geochemistry Of Volcanic Rocks From Homentioning
confidence: 97%
“…These rocks are unusually depleted in incompatible elements ( Fig. 5; Group D, TiO 2 = 0.7%-1.2%, Nb < 0.5-1.2 ppm, and Zr = 34-60 ppm), but have incompatible element ratios similar to normal I-type MORB as defined by Bryan et al (1976). The refractory nature of these basalts is.…”
Section: Igneous Petrology and Geochemistry Of Volcanic Rocks From Homentioning
confidence: 97%
“…The first studies of mid-ocean ridge basalts (MORB) resulted in the hypothesis that they represent a "window" to the mantle: an indicator of the mantle composition unaffected by continental contamination (Engel et al, 1965;Gast, 1965). Although these early studies emphasized the compositional uniformity of MORB, more extensive sampling has revealed considerable compositional variability, both locally and regionally (Schilling, 1973;Frey et al, 1974;Blanchard et al, 1976;Bryan et al, 1976;White et al, 1976). In particular, there are systematic trace element and isotopic gradients along the ridge crest near islands such as…”
Section: Chapter 4 Helium Isotopic Variations In Mid-ocean Ridge Basaltsmentioning
confidence: 99%
“…Similar typical Ba abundances of 12.2 ppm for Type I MORB and 55 ppm for Type II MORB are reported by the Basaltic Volcanism Study Project (1981). In comparison to Bryan et al's (1976) classification, Type I corresponds to basalt erupted along the "normal" topographic section of mid-ocean ridges and Type II corresponds to basalt produced at elevated sections of mid-ocean ridges adjacent to volcanic platforms associated with oceanic islands. Sr abundances in the Hole 504B basalts are also low (54-61 ppm), but are not as depleted as Ba abundances.…”
Section: Ree Ba and Sr Abundancesmentioning
confidence: 99%